Exploring the Relationship Between Entrepreneurial Experience, Government Support, and MSME Marketing Performance - Nurul Wardani Lubis (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in regional economic development, yet many still face limitations in marketing capability and institutional support, making entrepreneurial experience and government intervention essential factors in enhancing business performance. This study analyzes the influence of entrepreneurial experience and government support in improving the marketing performance of MSMEs fostered by the Deli Serdang Regency P3UD. The study was conducted on 115 MSMEs using Multiple Linear Regression. The results indicate that entrepreneurial experience and government support significantly influence marketing performance. Experience fosters prudence in business processes, while government support, although not yet optimal in providing expertise, proves crucial in facilitating licensing and promotion. This study highlights the importance of synergy between the internal capacity of entrepreneurs and the role of external government facilitators. The findings imply that strengthening entrepreneurs’ experiential capabilities alongside more targeted and skill-oriented government support is vital to achieving sustainable improvements in MSME marketing performance.